CHEMICAL AND ENERGETIC CHARACTERISTICS OF AFRICAN SWEET SORGHUM AS A SOURCE OF BIOENERGY - Caraschi,José C. (2019)
ABSTRACT The aim of this study was to evaluate the energetic potential achieved by the application of phyto-regulators to sweet sorghum cultivars. A randomized complete block design was used. Experiments were conducted using two sweet sorghum cultivars (BRS 508 and BRS 509), fourphyto-regulators (ethephon, ethyl-trinexapac, glyphosate, and sulfometuron-methyl), and a control; four replicates were performed 70 days after sowing, at the beginning of the flowering phase of the plants, with the aid of a CO2-pressurized coastal sprayer. The plants were harvested after 40 days, with the stems being cleared at the height of the apical bud, and were subjected to grinding for the extraction of broth. The following analyses were carried out: chemical (total extractives, lignin, and holocellulose contents), proximate (volatile matter, fixed carbon, and ash contents), and energetic (higher heating value). Multiple comparison (Tukey) and linear correlation (Pearson) analyses were carried out at a 5% significance level. The phyto-regulators positively and significantly influenced the chemical attributes and contents of lignin and fixed carbon. It was concluded that glyphosate, sulfometuron-methyl, and ethephon enhanced the biomass/bioenergy potential of sweet sorghum cultivars.